E-Satisfaction as A Reflection of E-Marketing and E-Sequal in Influencing E-Loyalty on E-Commerce - A. Manaf, Peri; Rachmawati, Ivany; Witanto, Marcella; Nugroho, Adityo (International Journal of Engineering and Technology, 2018)
Online shopping is becoming a trend in Indonesia. Seeing the trend m  any new e-commerce began to emerge. And the consumer will try to find out which marketplace can meet their expectations. The purpose of this study is to propose an integrative model of the e-loyalty development process and to test the model empirically and see how big the influence between e-marketing and e-service quality toward e-loyalty mediated by e-satisfaction. For this purpose, data was collected from a sample of 100 consumers in Java Island ie Banten, DKI Jakarta, DI Yogyakarta, West Java, Central Java, and East Java. The selection of samples was done by purposive sampling. The data used in this study is the primary data. SmartPLS has been used for data analysis. Data was analyzed to obtain hypothesis test. The study showed e-loyalty customers at E-Commerce’s website in Indonesia are influenced by e-satisfaction, where e-satisfaction is influenced by e-sequal and e-marketing. Moreover, the result also showed e-sequal affects e-loyalty more strongly than e-marketing with e-satisfaction as mediator.